Problems of philosophy - "Russell, Bertrand" (USA, 2009)
Appearance And Reality - The Existence Of Matter - The Nature Of Matter - Idealism - Knowledge By Acquaintance And Knowledge By Description - On Induction - On Our Knowledge Of General Principles - How A Priori Knowledge Is Possible - The World Of Universals - On Our Knowledge Of Universals - On Intuitive Knowledge - Truth And Falsehood - Knowledge, Error, And Probable Opinion - The Limits Of Philosophical Knowledge - The Value Of Philosophy - Bibliographical Note
Keywords: Philosophy